Multinationality and systematic risk: a literature review and meta-analysis - Christin Höge-Junge; Stefan Eckert (Management Review Quarterly, 2022)
In the literature, the impact of multinationality on the valuation of multinational companies is heavily debated. To understand this impact on valuation, we need to clarify whether and how multinationality affects systematic risk. For this purpose, we analyze the state of research concerning the impact of corporate multinationality on systematic risk, conducting a systematic literature review of 35 studies and a univariate meta-analysis based on 20 studies. We test the predictions of the upstream–downstream hypothesis and the increasing capital market integration hypothesis on the basis of a meta-regression analysis of 17 studies. Our results provide no empirical support for the upstream–downstream hypothesis. However, they corroborate the capital market integration hypothesis in a more radical manner than expected: whereas multinationality seemed to have a risk-reducing effect until the beginning of the 1990s, since then its impact appears to have shifted. We find a risk-increasing effect for multinationality from 1990 on. Our results have important implications for academic research and managerial practice.
Keywords: F23; F30; G11; G31; G32; L25; M16; 650; Multinationality; Systematic risk; Capital market integration; Upstream–downstream-hypothesis; Univariate meta-analysis; Meta-regression analysis